Estudio del grado de accesibilidad para personas con discapacidad física, en los atractivos turísticos del cantón Macará - Alvarado Estrada., Karen Jimabel (2023)
The Macará canton is the fourth largest and most populated urban in the province of Loja, located in southern Ecuador, its economy is based on agriculture, livestock, trade and tourism, being located in the border area with Peru. The general objective of this research was to determine the degree of accessibility for people with physical disabilities in the tourist attractions of the Macará canton; likewise, there were two specific objectives: To identify the degree of accessibility in the tourist attractions, for which the environment was described, through a site profile of the canton, an analysis of the tourist plant registered and not registered according to the regulations of accessible tourist services in Ecuador, updating the information in the inventory of attractions through MINTUR summary sheets, determining the accessibility of the attractions through the MINTUR accessibility sheet, preparing a matrix of strengths, weaknesses, opportunities and threats (SWOT), validating the diagnosis and preparing a cross SWOT. The second objective was to design improvement strategies, for which solutions to the problems identified in objective one was proposed through a strategy plan based on Marvin Blanco's methodology, and finally, the proposals were validated through a meeting with key authors of the research. Among the results obtained, it was determined that the Jorupe Reserve has 63% accessibility, being one of the eight tourist attractions with the highest percentage; also, more than 50% of the tourist plant does not comply with the inclusive criteria. The strategies that will help barrier-free tourism in the canton are determined by: Training on accessible tourism and social inclusion, designing a proposal for tourist and inclusive signage in the attractions, improving and adapting accessible tourism infrastructure.